Indigenous place names continued existence as markers of Indigenous identity in Sabah - Jeannet Stephen; Jabil Mapjabil; Nor Arifah Mohd Nor; Patricia Antoinette P. Lajumin; Reany Koton; Johan Johnes (Academic Inspired Network (AIN), 2021)
Indigenous place names reflect not only the uniqueness of a community’s cultural heritage but also serve as a tie to the rich history of the place. By the time the United Nation’s International Decade of Indigenous Languages is officially launched in 2022, Sabah can vouch its contribution to the international initiative in Sabah’s ability to maintain the various Indigenous place names in the state and consequently preserving Sabah’s cultural heritage identity. Thus far, studies have yet to be conducted on Indigenous place names in Sabah from the toponyms or geographical names on the colonial maps of North Borneo, now known as Sabah. In this article, the authors examine the place names found on the colonial maps of North Borneo. Researching from the framework of critical place inquiry (McKenzie & Tuck, 2015) and using document content analysis as the method of study, the authors found that, to date, many place names on the colonial maps of North Borneo are either exactly the same or having only slightly different spelling. The maps of North Borneo are in themselves a repository rich with materials that provide evidence for comparison basis on the preservation of Indigenous place name. An encouraging aspect that the researchers found is, in contrast to practices that replace Indigenous place names with other names for this or that reason, that many Indigenous place names on the colonial maps of North Borneo still existing to this day in Sabah points to the positive maintenance of Indigenous identity within modern settings.